The BGO Calorimeter of BGO-OD Experiment. (13th February 2015) - Bantes, B; Bayadilov, D; Beck, R; Becker, M; Bella, A; Bielefeldt, P; Bieling, J; Bleckwenn, M; Böse, S; Braghieri, A; Brinkmann, K-Th; Burdeynyi, D; et al.
Abstract: The BGO Rugby Ball is a large solid angle electromagnetic calorimeter now installed in the ELSA Facility in Bonn. The BGO is operating in the BGO-OD experiment aiming to study meson photoproduction off proton and neutron induced by a Bremsstrahlung polarized gamma beam of energies from 0.2 to 3.2 GeV and an intensity of 5 × 10 7 photons per second. The scintillating material characteristics and the photomultiplier read-out make this detector particularly suited for the detection of medium energy photons and electrons with very good energy resolution. The detector has been equipped with a new electronics read-out system, consisting of 30 sampling ADC Wie-Ne-R modules which perform the off-line reconstruction of the signal start-time allowing for a good timing resolution. Performances in linearity, resolution and time response have been carefully tested at the Beam Test Facility of the INFN National Laboratories in Frascati by using a matrix of 7 BGO crystals coupled to photomultipliers and equipped with the Wie-Ne-R sampling ADCs.